The Development of the Theory of Sovereignty and the Modern Law of Nations from Machiavelli to Grotius - Mehmet Emin Büyük (İstanbul Hukuk Mecmuası)
Political thought that continued until the Middle Ages, has been transformed both in the field of sociology and politics and in the theoretical field, alongside modernity. The keyword for this transformation is sovereignty. Sovereignty brings the relationship between auctoritas and potestas, which was previously sought in an external source, to a mundane level. Machiavelli was one of the first to see this change and went beyond a priori judgments brought by medieval political thought, leaving it to Bodin to replace the legitimacy relationship that he destroyed. Sovereignty is an inherent element of the state. It is absolute, perpetual, one, and indivisible. A true sovereign is one who possesses all these. Ultimately, basing legitimacy on a divine source―which was the missing point in Bodin’s definition of the secular state― became a component of the framework drawn by Suárez, which was based on the social contract theory. The modern states that emerged manifested their sovereignty in various ways, both internally and externally. The relations of such sovereign structures with each other achieved order within the system of international law. Vitoria foresaw modern international law regulating such a relationship between equals. Suárez rethought the facts seen by his predecessor with a positivist interpretation. Grotius took his place as the founder of modern international law by systematizing these previous interpretations. The current structure of international law is based on this background.